Metabolic Adaptations in Cancer Stem Cells - Yadav, Umesh Prasad; Singh, Tashvinder; Kumar, Pramit; Sharma, Praveen; Kaur, Harsimrat; Sharma, Sadhana; Singh, Sandeep; Kumar, Santosh; Mehta, Kapil (Frontiers in Oncology, 2020)
Cancer stem cells (CSCs) are a small and elusive subpopulation of self-renewing cancer cells with remarkable ability to initiate, propagate, and spread the malignant disease. In addition, they exhibit increased resistance to anticancer therapies, thereby contributing to disease relapse. CSCs are reported to be present in many tumor types such as melanoma, sarcoma, mammary tumors, colon cancer and other solid tumors. These cells from different tumors show unique energetic and metabolic pathways. For example, CSCs from one type of tumor may predominantly use aerobic glycolysis, while from another tumor type may utilize oxidative phosphorylation. Most commonly these cells use fatty acid oxidation and ketone bodies as the main source of energy production. CSCs have a remarkable ability to reprogram their metabolism in order to survive under adverse conditions such as hypoxia, acidosis, and starvation. There is increasing interest to identify molecular targets that can be utilized to kill CSCs and to control their growth. In this review, we discuss how an understanding of the unique metabolism of CSCs from different tumors can offer promising strategies for targeting CSCs and hence to prevent disease relapse and to treat the metastatic disease.